PREPARATION AND CHARACTERIZATION OF ZINC CROSSLINKED CHITOSAN MEMBRANE AS AN EFFECTIVE ADSORPTION MATERIAL FOR AMOXICILLIN IN PHARMACEUTICAL WASTEWATER - Azlan bin Kamari (Tanjung Malim, 2024)
PREPARATION AND CHARACTERIZATION OF ZINC CROSSLINKED CHITOSAN MEMBRANE AS AN EFFECTIVE ADSORPTION MATERIAL FOR AMOXICILLIN IN PHARMACEUTICAL WASTEWATER by Azlan bin Kamari